Evaluation of Percutaneous Peritoneal Drainage in High-Risk Patients with Perforated Peritonitis - Muhammad Hamayun Khan, Aftab Hussain, Aftab Alam, Aziz Ur Rehman, Iram Bashir, Sohaib Mohammad Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Perforated peritonitis is a critical condition associated with high mortality, especially in high-risk patients. Percutaneous peritoneal drainage (PPD) has emerged as a promising intervention for stabilizing these patients before surgery. Objective: This study aims to evaluate the efficacy and safety of PPD in 105 high-risk patients diagnosed with perforated peritonitis. Methods: A prospective cohort study was conducted from July to June 2023 at Department of surgery DHQ / Mufti Mehmood Teaching hospital and Gomal Medical college Dera ismail khan. A total of 105 high-risk patients with perforated peritonitis underwent PPD. Outcomes were assessed in terms of hemodynamic stabilization, reduction in septic load, and survival rates. Results: The survival rate post-procedure was 74%, with a 26% mortality rate. Significant improvements were observed in blood pressure, urine output, and white blood cell count. Mortality was higher in patients with pre-existing comorbidities, particularly ischemic heart disease. Conclusion: PPD is an effective intervention for stabilizing high-risk patients with perforated peritonitis. It improves survival rates and surgical outcomes by reducing septic load and enhancing clinical stability. Keywords: Percutaneous peritoneal drainage, perforated peritonitis, high-risk patients, septic load, surgery, mortality.